OIL SANCTIONS AGAINST IRAN : ECONOMIC AND REGIONAL IMPACTS - MohammadGhorbani, Ahmadreza; Bolotov, Ilya; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Abstract The present research aimed to analyse the impact of sanctions imposed on Iran’s oil and how such sanctions have influenced the socio-economic performance of Iran. This study will evaluate the broader national impacts of sanctions on imports, exports, GDP, GDP per capita, manufacturing, FDI, literacy rate, and unemployment. The author collected secondary data. The data analysis was conducted in two software programs, i.e. Microsoft Excel and Statistical Package for Social Sciences (SPSS). At the very first, the data was collected from the Macrotrends website, and it was organised in Microsoft Excel. Since the collected data was time series data, therefore, the line charts were plotted from the data in Microsoft Excel, and then the data was exported to the Statistical Package for Social Sciences (SPSS). The linear regression analysis was conducted in SPSS to reveal the association of GDP per capita, exports, imports, FDI, and manufacturing with the GDP of Iran. The data indicated that exports, imports, FDI, GDP, GDP per capita, and manufacturing significantly decreased in the years from 1987 to 1995. The drastic variation and decrease in the economic stability of Iran were due to the imposed sanctions by the US. The social impacts over the years (1979-2023) are observed to be progressive. For example, the poverty rate of Iran has reduced from 52.90% in 1986 to 21.90% in 2022, and the literacy rate increased from 36.52% in 1976 to 89.96% in 2022. From the social perspective, the country has performed well, whereas the economic impacts have significantly damaged the Iranian economy. The association of all the variables (GDP per capita, exports, imports, manufacturing, and FDI) with the GDP of Iran was revealed by conducting the regression analysis. The results of regression analysis indicated that GDP per capita, exports, imports, manufacturing, and FDI were strongly and positively associated with the GDP of Iran.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses